2018
DOI: 10.1371/journal.pone.0191984
|View full text |Cite
|
Sign up to set email alerts
|

A new compound of thiophenylated pyridazinone IMB5043 showing potent antitumor efficacy through ATM-Chk2 pathway

Abstract: Through cell-based screening models, we have identified a new compound IMB5043, a thiophenylated pyridazinone, which exerted cytotoxicity against cancer cells. In the present study, we evaluated its antitumor efficacy and the possible mechanism. By MTT assay, IMB5043 inhibited the proliferation of various human cancer cells lines, especially hepatocarcinoma SMMC-7721 cells. IMB5043 blocked cell cycle with G2/M arrest, induced cell apoptosis, and inhibited the migration and invasion of SMMC-7721 cells. As verif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 38 publications
0
12
0
Order By: Relevance
“…This process causes DNA fragmentation, cytoskeleton degradation, and disintegration of the cell into apoptotic bodies (Elmore 2007; Wu and Bratton 2013). The involvement of caspase-3-induced apoptosis has been previously shown for other pyridazinone derivatives (Gong et al 2018). Interestingly, other studies have shown that oxidative stress can negatively regulate caspase-3 activation (Huang et al 2008; Lee and Shacter 2000; Rossig et al 1999).…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…This process causes DNA fragmentation, cytoskeleton degradation, and disintegration of the cell into apoptotic bodies (Elmore 2007; Wu and Bratton 2013). The involvement of caspase-3-induced apoptosis has been previously shown for other pyridazinone derivatives (Gong et al 2018). Interestingly, other studies have shown that oxidative stress can negatively regulate caspase-3 activation (Huang et al 2008; Lee and Shacter 2000; Rossig et al 1999).…”
Section: Discussionmentioning
confidence: 61%
“…Under homeostasis, phosphatidylserine (PS) is found preferentially in the inner leaflet (cytosolic) of the plasma membrane, but upon cell death induction, it is translocated to the outer leaflet and serves as a sensitive indicator of cells undergoing apoptosis (Leventis and Grinstein 2010). It was previously reported that a pyridazinone (IMB5043) induced apoptosis via PS externalization in the human SMMC-7721 hepatoma cell line (Gong et al 2018). In addition, increased ROS production resulted in phosphatidylserine oxidation and facilitated the PS extemalization to the plasma membrane in HL-60 cells (Matsura et al 2002).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, compounds 4aa and 4ba induced a similar increase of intracellular cAMP in both cell types, despite a differential response having been highlighted by Sun et al, who studied the anti-cancer effect of zardaverine in different hepatocarcinoma cell lines [ 44 ]. Another hypothesis relies on the fact that PDE4 inhibitors possessing a pyridazinone scaffold could exhibit anti-cancer effects independently of PDE4 activity, as demonstrated by Sun et al Among hypotheses to investigate further, the pyridazinone-based compound inhibition of c-Met kinase, activation of ATM-Chk2 pathway and ROS accumulation and proteasome function impairment have already been suggested [ 45 , 46 , 47 ]. These could explain part of our results, since zardaverine induced a high increase of intracellular cAMP and a slight decrease in cell proliferation, contrary to the effects of compounds 4aa and 4ba .…”
Section: Discussionmentioning
confidence: 99%
“…By histopathological study, no lesions were found in bone marrow and various organs of the treated mice. IMB5043 is as an active compound consisting of both pyridazinone and thiophene moieties exerts antitumor efficacy through activation of ATM-Chk2 pathway and may serve as a promising leading compound for the development of antitumor drugs (Gong at al., 2018).…”
Section: Biological Activitiesmentioning
confidence: 99%